Harassing habitats : experienced space in Finnish contemporary fiction : a study on Maarit Verronen - Kankkunen, Sarianna; Helsingin yliopisto. Humanistinen tiedekunta; Unigrafia (yhtiö) (Faculty of Arts, University of Helsinki, 2021)
Abstract.
Keywords: kirjallisuudentutkimus; spekulatiivinen fiktio; tila; litteraturvetenskap; spekulativ fiktion; utrymme